From machinery to mobility : government and democracy in a participative age - Roy, Jeffrey (Public Administration and Information Technology, 2013)
The Westminster-stylized model of Parliamentary democratic politics and public service accountability is increasingly out of step with the realities of today's digitally and socially networked era. This book explores the reconfiguration of democratic and managerial governance within democratic societies due to the advent of technological mobility. More specifically, the traditional public sector prism of organizational and accountability - denoted as 'machinery of government', is increasingly strained in an era characterized by smart devices, social media, and cloud computing. This book examines the roots and implications of the tensions between machinery and mobility and the sorts of investments and initiatives that have been undertaken by governments around the world as well as their appropriateness and relative impacts. This book also examines the prospects for holistic adaptation of democratic and managerial systems going forward, identifying the most crucial directions and determinants for improving public sector performance in terms of outcomes, accountability, and agility. Accordingly, the ultimate aim of this initiative is to contribute to the formation of intellectual foundations for more systemic reforms of public sector governance in Canada and elsewhere, and to offer forward-looking trajectories for government adaptation in shifting from a traditional prism of 'machinery' to new organizational and institutional arrangements better suited for an era of 'mobility'.